(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
The kidney is one of the crucial organs to maintain proper homeostasis in the body, and develop nephroprotective agents to retain kidney health and an absolute requisite. Since plant-based medicine gained importance due to fewer side effects and more safety, a herbal approach to develop nephroprotective agents is still necessary. Our present investigation is aimed to screen the antioxidant and nephroprotective activity of Alphonsea sclerocarpa leaves. Wistar rats were used in the current paracetamol-induced nephrotoxicity model through standard experimental procedures. N-acetyl cysteine (NAC) is taken as standard, the flavonoid-rich fraction of A. sclerocarpa was given to the animals in two doses (200 and 400 mg/kg body weight) for seven days. After the treatment, blood samples were collected from all the animals and sacrificed for histopathological studies. To support this investigation, phytochemical screening, total phenolic, flavonoid, tannin contents were also determined. The antioxidant activity studies by DPPH assay, NO free radical scavenging assay, and total antioxidant assay were also screened using standard protocols. Results unveil that the plant is rich in polyphenolic contents, and the flavonoid-rich fraction has statistically significant (P<0.001) nephroprotective activity in a dose-dependent manner compared to the standard N-acetyl cysteine. The biochemical and histological studies were also conducted in connection with the titled activity and found significant to improve the abnormal blood parameters and enzymatic and non-enzymatic antioxidants in the kidney tissue. To wrap up, all the biochemical, behavioral, and histological data declared that the flavonoid-rich fraction of A. sclerocarpa is more potent among all the extracts to protect against oxidative stress and subsequent improvement of the physiological parameters of the kidney. The antioxidant property of the phytochemicals present in the extract may be responsible for the affirmed activity.